Dynamics of Law Enforcement of the Islamic Criminal Law in Aceh in the Indonesian Democratic System - Rabiatul Adawiah; Ihsan Kamaludin (Islam Transformatif : Journal of Islamic Studies, 2021)
This study focuses on analyzing the dynamics of the application of the Criminal Code (Qanun Jinayah) in the Aceh region. In the Pancasila democratic system run by the Indonesian state, the government guarantees the right of every citizen and belief group to manifest their teachings, but there are some areas that have the authority to enforce special policies such as Aceh which has ratified regional regulations based on Islamic law and the State supports the application of the rules. the. The method used in this study is descriptive qualitative research expected to be able to reveal qualitative information with description-analysis using the strategy used in this research is a case study. This research indicates that the implementation of Qanun Jinayah carried out in Aceh often results in differences of opinion because some parties consider that the application of the law overlaps with human rights which is usually implemented in democratic countries such as Indonesia, moreover the law also applies to non-Muslim residents who live in Aceh. However, there are also several parties who continue to support the implementation of the Qanun Jinayah to continue to be enforced because they have followed special rules ratified by the Government of Indonesia. Penelitian ini berfokus untuk menganalisa dinamika penerapan Peraturan Tindak Pidana (Qanun Jinayah) di wilayah Aceh. Di dalam sistem demokrasi Pancasila yang dijalankan oleh negara Indonesia, pemerintah menjamin hak setiap warga negara maupun kelompok kepercayaan untuk memanifestasikan ajarannya, namun terdapat beberapa wilayah yang memiliki otoritas untuk memberlakukan kebijakan khusus seperti Aceh yang telah mengesahkan peraturan daerah bedasarkan syariat Islam dan Negara mendukung penerapan aturan tersebutMetode yang digunakan di dalam penelitian ini adalah kualitatif deskriptif yang dimaksudkan untuk menganalisa topik secara mendalam serta menggunakan strategi studi kasus. Penelitian ini mengindikasikan bahwa penerapan Qanun Jinayah yang dilakukan di Aceh sering kali menghasilkan perbedaan pendapat dikarenakan beberapa pihak menilai bahwa penerapan hukum tersebut tumpang tindih dengan hak asasi manusia, apalagi hukum tersebut juga berlaku bagi penduduk non-muslim yang tinggal di daerah Aceh. Meskipun demikian, terdapat juga beberapa pihak yang terus mendukung penerapan Qanun Jinayah tersebut untuk dapat terus diberlakukan karena sudah mengikuti aturan khusus yang disahkan oleh Pemerintah Indonesia